Nano-fertilizers: The future of nutrient approaches for cereals - R, SANTHOSH BABU; M, JOSEPH; M, HEMALATHA; J, BHUVANESWARI; S, SRINIVASAN; D, LENINRAJA (The Indian Journal of Agricultural Sciences, 2024)
Nanotechnology offers a promising solution to address the nutrient demands of cereals, which are nutrient-intensive crops typically reliant on large amounts of inorganic fertilizers. These large quantities of nutrients are supplied to the crop by applying a huge amount of inorganic fertilizer as a soil application led to a decline in environmental systems, particularly affecting the soil health, lesser use efficiency of fertilizers and water resources contamination. In this context, nanotechnology serves as a potential solution. The huge demand for nutrients in cereal crops is met by nano-fertilizers. The nano-fertilizers are now playing a promising role in fulfilling the nutrient requirement of the crops by replacing the normal conventional fertilizers not only for cereals but also for other agricultural crops. The mechanism of action of nano-fertilizers is that they are smaller than the pore size of plant cell walls, allowing them to easily enter and reach the plasma membrane. Nano-fertilizers have 100 times greater surface area than conventional fertilizers, allowing them to easily interact with plant surfaces and increase the absorption of nutrients. Therefore, the nutrient-use efficiency of the crop is increased and shown a positive effect on the physiological and growth parameters of cereal crops, resulting in enhanced yield and improved drought tolerance. This review discussed, the effects and efficiency of nano-fertilizers on cereal crop growth and the correlation between physiological, qualitative, quantitative traits with nano-form of application in detailed manner. This review concludes that nano-fertilizers are the potential nutrient source for cereal crops like rice (Oryza sativa L.), wheat (Triticum aestivum L.), maize (Zea mays) etc. and they are going to be a promising resource for nutrient management in agricultural crops.